PENDUGAAN ELASTISIAS PERMINTAAN INPUT PADA USAHATANI WORTEL DI DESA SUMBER BRANTAS KECAMATAN BUMIAJI KOTA BATU - Farhatul Qolbi; Bambang Siswadi; Masyhuri Mahfudz (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
AbstractThis study objectives is to analyze the effect of production factors on the benefits of carrot farming and predict the elasticity of input demand on carrot farming in Sumber Berantas Village, Batu City. Location selection was done purposively by using data collection methods using simple random sampling using a sample of 60 carrot farmers. Data analysis used using descriptive analysis, Cobb Douglas production function analysis and Douglas method (UOP-CDPF) Output Price Unit or UOP of Cobb Douglass Profit Function. Based on the results of analysis using the Cobb-Douglass UOP profit function the Output Price Unit or UOP of Cobb Douglass Profit Function (UOP-CDPF) is obtained by factors that influence the profit function seen from the results of the t test. the results of carrot production are manure, NPK fertilizer and medicine because it has a value of P <0.05. The calculated F value is obtained at 14.60 with a probability of 0,000 or less than 0.05 at a confidence level of 99%. Elasticity of input demand: (a) Price elasticity of demand is elastic for variable seeds, manure, urea, NPK fertilizer, ZA fertilizer, drugs and labor inelastic because of the value Ep> 1. (b) The elasticity of cross-price requests for all variables, namely seeds, manure, urea, NPK fertilizer, ZA fertilizer, drugs and labor are complementary, because the Ep value is <0 or -1. (c) Eelasticity of variable input demandfor fixed or income inputs (icome elasticity). of all variables, namely seeds, manure, urea, NPK fertilizer, ZA fertilizer, drugs and labor are inferior, because they have a value of Ei <1.Keywords: The elasticity, of the request